2018
DOI: 10.15640/jcsit.v6n2a5
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Application in Biomedical Signals

Abstract: Recent improvements in big data and machine learning have enhanced the importance of biomedical signal and image-processing research. One part of machine learning evolution is deep learning networks. Deep learning networks are designed for the task of exploiting compositional structure in data. The golden age of the deep learning network in particular convolutional neural networks (CNNs) began in 2012. CNNs have rapidly become a methodology of optimal choice for analysing biomedical signals. CNNs have been suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 86 publications
0
15
0
1
Order By: Relevance
“…Simple CNN, ResNet, WaveNet, and Inception are among the best CNNs networks widely used in biomedical signals analysis studies. Based on recent works [ 42 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ], a comparative analysis is provided in the following using various performance criteria as complexity , 1D-dimension , performance and time-consumption . In this regard, specific three tests (2, 3 and 4 states) with various values are given for each criterion as following.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple CNN, ResNet, WaveNet, and Inception are among the best CNNs networks widely used in biomedical signals analysis studies. Based on recent works [ 42 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ], a comparative analysis is provided in the following using various performance criteria as complexity , 1D-dimension , performance and time-consumption . In this regard, specific three tests (2, 3 and 4 states) with various values are given for each criterion as following.…”
Section: Methodsmentioning
confidence: 99%
“…Various DL models have been applied to biomedical signal analysis [ 36 ] particularly for recurrent neural networks (RNNs) [ 37 ], long short-term memory (LSTM) [ 38 ], auto-encoder (AE) [ 39 ], convolutional neural networks (CNNs) [ 40 ], deep stacking networks (DSNs) [ 41 ], etc. Among them, CNNs models [ 42 ] are the most frequently used in biomedical signals classification for anomaly detection due to its high classification accuracy. In this sense, several biomedical signals-based CNNs studies [ 43 , 44 , 45 ] have been suggested for anomaly detection tasks using various architectures such as CNN, visual geometry group network (VGGNet), Residual Network (ResNet), Dense Net, Inception Net, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The operating frequencies of various signals are not determined due to the presence of diverse designs, resulting in a miscount of separate integration gates. As a starting point, neural networks are useful for processing crucial signals because they take advantage of a variety of compositional properties of biological points of representation ( 10 ). Furthermore, if any problems are found in a large structure, ECG and EEG data will be isolated, allowing for future orientations and change.…”
Section: Survey Of Conventional Modelsmentioning
confidence: 99%
“…electroencephalogram, electromyography and so forth [104,105]. As illustrated in Figure 5, this method transforms a time series into polar coordinates and then into Gramian Angular Fields (GAF) images [105], i.e., the visual representation of the Gramian matrix, a linear algebra structure used to compute linear independence.…”
Section: Deep Generative Modelsmentioning
confidence: 99%
“…Inspired by recent successes of DL in computer vision and speech recognition, a promising relatively recent methodology has been proposed to encode time series data as images and to classify them using techniques from computer vision, which can be used to apply DL models to analyze various physiological signals such as heart rate, electrocardiogram, electroencephalogram, electromyography and so forth [ 103 , 104 ]. As illustrated in Figure 5 , this method transforms a time series into polar coordinates and then into Gramian Angular Fields (GAF) images [ 104 ], i.e.…”
Section: Enhancing Data Analytics In Medicine With DLmentioning
confidence: 99%